Estimation of the productive potential of the Santander goat based on morphometric measurements and body índices - Torres Ruda, Daniel Felipe (Spei Domus, 2025)
Introduction: The Santandereana goat, recognized as an indigenous zoogenetic resource of the Santander department, plays a fundamental role in the rural economy and food security of arid zones in the Chicamocha Canyon. This study aimed to evaluate the productive capacity of young males by analyzing morphometric variables and body composition indices throughout their growth. Methods: Twenty-seven males of the breed were used, distributed into three age groups (4, 8, and 12 months), and maintained under controlled management and feeding conditions. Ten morphometric variables were evaluated: weight (kg), height at the withers (cm), height at the croup (cm), thoracic circumference (cm), abdominal circumference (cm), body length (cm), hip width (cm), hip length (cm), testicular circumference (cm), and testicular diameter (cm), along with the following indices: Body Composition Index (BCI), Lateral Body Composition Index (LBCI), Compactness Index, Anamorphosis Index (ANI), Pelvic Index (PIE), Transverse Pelvic Index (TPI), Longitudinal Pelvic Index (LPI), and Relative Thoracic Depth Index (RTPI). Results: The studies showed a progressive increase in body weight and morphological dimensions with age, with statistically significant differences (p<0.05) in most variables between groups. Weight, thoracic circumference, and testicular circumference were identified as relevant indicators of development and sexual maturity. These findings allow for the establishment of useful morphometric criteria for the productive and reproductive classification of this native breed. Conclusions: The results identified the productive potential for meat production and its application in selection and genetic improvement programs aimed at the sustainability of goat farming systems in semi-arid regions of Colombia.